Psycho-Emotional Sphere in Patients with Peptic Ulcer, What’s Wrong? - Saidovich, Kadirov Bekhruzbek (Journal of Science in Medicine and Life, 2024)
Autonomic dystonia is significantly more likely to be detected in patients with gastric ulcer than in healthy people. Under the influence of dysfunction of the autonomic nervous system, factors contribute to the formation of ulcers, such as impaired regional blood flow, motility, acid formation, creating conditions for the persistence of Helicobacter pylori. A comprehensive assessment of the vegetative status allows you to adequately assess the symptoms of gastric ulcer and to correct treatment taking into account violations of the tone of the autonomic nervous system.